Distribution, abundance, and habitats of rare species Parnopes grandior (Pallas 1771) (Hymenoptera, Chrysididae) in Mordovia and adjacent regions, Russia - ALEXANDER B. RUCHIN; ALEXANDER V. ANTROPOV; ANATOLIY A. KHAPUGIN (Society for Indonesian Biodiversity, 2019)
Ruchin AB, Antropov AV, Khapugin AA. 2019. Distribution, abundance, and habitats of rare species Parnopes grandior (Pallas 1771) (Hymenoptera, Chrysididae) in Mordovia and adjacent regions, Russia. Biodiversitas 20: 303-310. The study of biological and ecological characteristics is essential in conservation efforts of threatened and locally rare species. Obtaining the comparable data in different regions of a species range allows developing a conservation strategy. We aimed to study the distribution, acquired characteristics of the abundance and habitats of the biology of a rare species Parnopes grandior (Pallas, 1771) in the Republic of Mordovia (European Russia). As a result of our study, the biology of Parnopes grandior found in the Republic of Mordovia and in five adjacent regions (Volga River Basin, Russia) is described. In the Republic of Mordovia in 2008-2018, 18 habitats of this species were identified. In all cases, it was found next to the host wasp colonies of Bembix rostrata (Linnaeus, 1758). The species population was low (no more than five individuals per study site). In all the sites surveyed, it inhabited xerophytic plant communities on sandy disturbed substrate. In these habitats, the coverage of plants is low and does not exceed 20%. The list of plants visited by the adults of Parnopes grandior is given. In the adjacent regions, the species abundance is also not high, but the number of records and abundance increases significantly to the south of the Ulyanovsk region.